Miss Peregrine's Home for Peculiar Children : the graphic novel - Cassandra Jean.; Riggs, Ransom (New York, NY : Yen Press, 2013)
Presents a graphic novel adaption of Ransom Riggs' "Miss Peregrine's Home for Peculiar Children" in which sixteen-year-old Jacob, having traveled to a remote island after a family tragedy, discovers an abandoned orphanage, and, after some investigating, he learns the children who lived there may have been dangerous and quarantined and may also still be alive.
Young Adult
Young Adult
Keywords: Islands -- Comic books, strips, etc. -- Juvenile fiction; Orphanages -- Comic books, strips, etc. -- Juvenile fiction; Islands -- Fiction; Mystery and detective stories; Orphanages -- Fiction; Comic books, strips, etc; Graphic novels; Islands -- Comic books, strips, etc. -- Fiction; Mystery graphic novels; Orphanages -- Comic books, strips, etc. -- Fiction; Graphic novels; Mystery comic books, strips, etc